Estrategia de desarrollo local en la parroquia García Moreno, cantón Bolívar, mediante el sistema productivo con gallinas de postura - Valencia Bedón, Rosa Luz (2021)
The objective of this project is to design methodological concepts that contribute to improving the productive and economic system of the families of the García Moreno Parish, Bolívar canton, through the introduction and implementation of commercial egg-laying hens, as a local development strategy. . The research methodology that is developed is based on the quantitative and qualitative paradigm, it is descriptive and interpretative through data collection, its deduction and analytical interpretation. Application type research. The theoretical-practical result is specified in the design of a local development strategy that promotes the local development of the community in question. For them, the essential elements to be considered in poultry production practices at a local scale are synthesized, which constitutes a novelty insofar as the integration of knowledge and methodologies contained in the study is achieved to improve the local production system, through proper management and care of laying hens and the use of short marketing cycles, involving families in the activity, which shows results in increased poultry production and community income, a fact that favors the purpose not only of the community but also of Ecuadorian society. The tangible attributes in the egg make it a quality food. In relation to the intangible attributes, the valued factors correspond to a great extent to the nutritional contribution with respect to the commercial egg and the absence of chemical products or harmful substances. The actions contained in the strategy could be generalized in communities that present similar socio-productive and cultural conditions.